PENGARUH STRATEGI PEMASARAN MELALUI TIKTOK TERHADAP MINAT BELI KONSUMEN: STUDI LITERATUR - Annisa, Febri; Mochammad Reza Fadli; Novia Suherman; Ida Farida Adi Prawira (Jurnal Manajemen dan Pemasaran, 2024)
TikTok, with over 1 billion global active users, has become the platform of choice for business marketing, especially in Indonesia with 22.2 million active users. Businesses use TikTok to create engaging content, collaborate with influencers, and run paid advertisements. These marketing strategies aim to enhance brand awareness and foster interactions with consumers. Several studies have showcased TikTok campaigns' success, such as the "BFI Smile Ramadhan" campaign by BFI Finance. TikTok is also utilized to influence purchasing decisions, as demonstrated in a study involving a brand called Bittersweet by Najla. All of this underscores TikTok's crucial role in digital marketing. The research conducted aims to gather evidence through a literature review method based on existing studies regarding the Influence of TikTok Marketing on Consumer Purchase Intent.